Dissolving microneedles to obtain rapid local anesthetic effect of lidocaine at skin tissue. (28th June 2013) - Ito, Yukako; Ohta, Junichi; Imada, Kazuki; Akamatsu, Shingo; Tsuchida, Nozomi; Inoue, Genta; Inoue, Nana; Takada, Kanji
Abstract: Dissolving microneedles (DMs) were applied to lidocaine for local anesthesia of the skin. Three DM array chips were prepared where lidocaine was localized at the acral portion of DMs (type 1), loaded in whole DMs (type 2), and lidocaine was loaded both in whole DMs and the chip (type 3). DM chips were 15-mm diameter with 225 DMs, each 500-μm long with a 300-μm diameter base. The lidocaine contents were (type 1) 0.08 ± 0.01 mg, (type 2) 0.22 ± 0.01 mg and (type 3) 8.52 ± 0.49 mg. Lidocaine was released from type 1 and 2 DM array chips within 10 min. Pharmacological activity of DMs were compared to lidocaine cream by the suppression of idiospasm of hair-removed rat skin. Type 1, 2 and 3 DMs showed faster onset time, 5 min, than lidocaine cream. Type 2 and 3 DMs showed stronger anti-idioplasmic activity than type 1 DMs. Pharmacokinetic study showed that tissue lidocaine levels, 62.8 ± 3.6 (type 1), 89.1 ± 9.9 (type 2) and 131.2 ± 10.2(type 3) μg/g wet weight at 5 min after the removal of DM were obtained higher than lidocaine cream, 26.2 ± 12.5 μg/g wet weight. Those results suggest the usefulness of type 2 DMs to obtain fast onset time for the local anesthesia in the skin.